Assessment of nutritional status among elderly population in a rural area in Manipur: community-based cross-sectional study - O., Joymati; Ningombam, Minita; Rajkumari, Bishwalata; Gangmei, Agatha (International Journal Of Community Medicine And Public Health, 2018)
Background: Malnutrition in elderly (≥60 years) is both a health outcome as well as a risk factor for diseases. It increases the risk both of morbidity and mortality among them. Objectives of the study were to determine the prevalence of nutritional status among elderly people and any associated factors between nutritional status with selected variables of interest. Methods: This cross-sectional study was conducted from March to April, 2017 in a rural community in Kongpal in Imphal East, Manipur in North-Eastern India. Using a structured interview schedule, data were collected from 245 elderly people aged ≥60 years. For nutritional assessment, Mini nutritional assessment tool (MNA) was used. Descriptive statistics like mean (SD) and Chi-square test was used. P<0.05 was taken as significant. Results: A total of 250 eligible individuals participated. Mean age (SD) was 69.5 (±7.7) years and majority (82.4%) belonged to 60-74 age groups. Around three-fifth of the respondents (56.0%) reported they suffered from co-morbid illnesses. According to MNA tool, one-fifths (20.8%) of respondents were malnourished and 49.2% at risk of malnourished. Significant association was found between being malnourished with older age group, female gender, among unmarried/widow/widower, lower educational level, unemployed/ homemaker and financially dependent on other. Conclusions: The overall prevalence of malnutrition and at risk of malnutrition in our study was 20.8% and 49.2%. Approaches to improve the nutritional status of the elderly should focus primarily on those who are older, low educational status, female gender and financially dependence.